Circadian rhythm of salivary cortisol, plasma cortisol, and plasma ACTH in end-stage renal disease - Raff, Hershel (BioScientifica, 2012)
OBJECTIVE: Patients with end-stage renal disease (ESRD) can display the features of endogenous hypercortisolism but are difficult to evaluate for Cushing's syndrome. We evaluated the circadian rhythm of plasma compared with salivary cortisol in subjects with ESRD. DESIGN: Plasma and salivary cortisol and plasma ACTH samples were drawn frequently over 24 h in an inpatient research unit in stable ESRD subjects on daytime chronic hemodialysis (n=16) vs controls (n=8). METHODS: Plasma cortisol was measured every 2 h from 0800 to 0600 h the following day. Salivary cortisol was measured every 2 h, except between 2400 and 0400 h (sleep time). Plasma ACTH measured in a subset of samples and C-reactive protein (CRP) was measured as a marker of a subclinical inflammatory state in all subjects. RESULTS: ESRD subjects had a discernable circadian rhythm in plasma and salivary cortisol, but with a significantly higher nadir (1800–2400 h) compared with the controls (P=0.016–<0.001). After excluding four ESRD subjects without a normal circadian rhythm, the ESRD subjects still had higher nadir plasma and salivary cortisol and plasma ACTH compared with controls. There was no difference in the correlation of salivary and plasma cortisol in control vs ESRD subjects. ESRD subjects had higher CRP levels compared with controls. CONCLUSIONS: ESRD subjects had increased late-night plasma and salivary cortisol and plasma ACTH levels. Late-night salivary cortisol is a reliable index of plasma cortisol in ESRD patients.